Breast self-examination by Peruvian women: prevalence and social and demographic associated factors. Family Health Demography Survey (ENDES) analysis - Romaní, Franco (2011)
Introduction: Breast cancer is a global public health problem and the most common cancer among women. In Peru it is the second leading cause of cancer death in women. Mammography is the most common diagnostic tool; though breast self-examination is easy, inexpensive, and noninvasive. Objectives: To determine the frequency of breast self-examination in Peruvian women of childbearing age, and sociodemographic factors associated with this practice. Design: Analysis of secondary sources based on the Population and Family Health Survey (ENDES, Peru) 2008, a probabilistic, stratified and multistage sample study that investigated population dynamics and maternal and child health, including questions on breast self-examination performance. Setting: Urban and rural areas in all departments of Peru, including Lima. Participants: Nine thousand seven hundred and twenty-four women aged 20 to 49. Interventions: ENDES data collection method was by direct interview by visiting selected households for data collection. We performed bivariate and multivariate analysis of this sample to determine association between breast self-examination performance and sociodemographic characteristics of women surveyed. Main outcome measures: Prevalence and sociodemographic factors associated with breast selfexamination performance. Results: Breast self-examination was done by 34,6% of 20 to 49 year-old Peruvian women surveyed. Sociodemographic factors significantly associated to breast self-examination were: age between 30-39 and 40-49 years; being moderately wealthy, rich or very rich; having 1-2 children, and having had breast examination by a health professional in the past 5 years; for all cases p <0,05. Women in the high mountains and forests were less likely to perform breast self-examination. Conclusions: Only 34,6% of Peruvian women between 20 and 49 years performed breast self-examination. Factors associated with breast self-examination were being 30-49 year-old, moderately wealthy, rich or very rich, having 1-2 children, and having had breast examination by a health professional. Mammography coverage would be much lower in Peru.